A multimode interference polymer-silica hybrid waveguide 2×2 thermo-optic switch - Sun, X.Q.; Chen, C.M.; Wang, F.; Sun, J.; Gao, W.N.; Gao, L.; Zheng, H.L.; Kang, C.P.; Zhang, D.M. (Oficyna Wydawnicza Politechniki Wrocławskiej, 2010)
A polymer-silica hybrid 2×2 thermo-optic switch is demonstrated. The top cladding and core layer are composed of polymers, while the bottom cladding is made of silica. Since polymer and silica have opposite signs of thermo-optic coefficients, the change of the refractive index of the core is opposite to that of the bottom cladding as the temperature increased. With the finite difference beam propagation method (FD-BPM) and thermal coupling simulation, the proposed device presents a crosstalk of 20 and 18 dB at bar state and cross state, respectively. The device also exhibits extinction ratios of 19 and 27 dB at each state. In addition, the low absorption of material and simple structure of the device enable the insertion loss to be 17 dB. Also the electrical power consumption is about 45 mW at λ = 1.55 mm. The rise time and fall time of switching are 0.2 ms and 0.4 ms, respectively.
Optica Applicata, Vol. 40, 2010, nr 3, s. 737-745
Keywords: optyka; polymer waveguide device; thermo-optic effects; optical switches